PERILAKU KELUARGA DENGAN KEMANDIRIAN LANSIA DALAM PEMENUHAN AKTIVITAS SEHARI-HARI DI DESA HUTABOHU KECAMATAN LIMBOTO BARAT KABUPATEN GORONTALO - Andi Nuraina Sudirman; Rona Febriyona; Riskawaty Mamuki (Zaitun (Jurnal Ilmu Kesehatan), 2020)
This research was conducted to the elderly. The objective was to find out The Relationship between Family Behaviors with the Independence of the Elderly in Fulfilling Daily Activities at Hutabohu Village. The type of research used quantitative with analytic observation design with cross sectional study approach, and the sampling technique used purposive sampling, the sampling technique with certain considerations or criteria by using a questionnaire on 52 respondents. The result showed family’s good behavior with the independence of elderly which dependence are 2 respondents (7,4%), family’s behavior which is enough with the independence of elderly which dependence are 3 respondents (21,4%), and the less of family’s behaviour with the independence of elderly which dependence are 8 respondents (72,7%). While family’s good behavior with the independence of elderly are 25 respondents (92,6%), family’s behavior which is enough with the independence of elderly are 11 respondents (78,6%), and the less of family’s behaviour with the independence are 3 respondents (27,3%), with Chi-square test result is p-value = 0,000 small than α ≤0,05. Concluded there is relationship between Family Behaviors with the Independence of the Elderly in Fulfilling Daily Activities at Hutabohu Village, Limboto barat sub district of Gorontalo district.